Adiponectin attenuates profibrotic extracellular matrix remodeling following cardiac injury by up‐regulating matrix metalloproteinase 9 expression in mice. Issue 24 (21st December 2017) - Jenke, Alexander; Schur, Robert; Röger, Carsten; Karadeniz, Zehra; Grüger, Mathias; Holzhauser, Luise; Savvatis, Kostas; Poller, Wolfgang; Schultheiss, Heinz‐Peter; Landmesser, Ulf; Skurk, Carsten
Abstract: Adiponectin (APN) is a multifunctional adipocytokine that inhibits myocardial fibrosis, dilatation, and left ventricular (LV) dysfunction after myocardial infarction (MI). Coxsackievirus B3 (CVB3) myocarditis is associated with intense extracellular matrix (ECM) remodeling which might progress to dilated cardiomyopathy. Here, we investigated in experimental CVB3 myocarditis whether APN inhibits adverse ECM remodeling following cardiac injury by affecting matrix metalloproteinase (MMP) expression. Cardiac injury was induced by CVB3 infection in APN knockout (APN‐KO) and wild‐type (WT) mice. Expression and activity of MMPs was quantified by qRT‐PCR and zymography, respectively. Activation of protein kinases was assessed by immunoblot. In cardiac myocytes and fibroblasts APN up‐regulates MMP‐9 expression via activation of 5′ adenosine monophosphate‐activated protein kinase (AMPK) and extracellular signal‐regulated kinase (ERK)1/2 which function as master regulators of inflammation‐induced MMP‐9 expression. Correspondingly, APN further increased up‐regulation of MMP‐9 expression triggered by tumor necrosis factor (TNF)α, lipopolysaccharide (LPS) and R‐848 in cardiac fibroblasts. In vivo, compared to WT mice cardiac MMP‐9 activity and serum levels of carboxy‐terminal telopeptide of type I collagen (ICTP) were attenuated in APN‐KO mice in subacute (day 7 p.i.) CVB3 myocarditis. Moreover, on day 3 and day 7 post CVB3 infection splenic MMP‐9 expression was diminished in APN‐KO mice correlating with attenuated myocardial immune cell infiltration in subacute CVB3 myocarditis. These results indicate that APN attenuates adverse cardiac remodeling following cardiac injury by up‐regulating MMP‐9 expression in cardiac and immune cells. Thus, APN mediates intensified collagen cleavage that might explain inhibition of LV fibrosis and dysfunction. Abstract : Our study investigates in experimental CVB3 myocarditis whether the adipokine adiponectin (APN) inhibits adverse ECM remodeling by affecting matrix metalloproteinase (MMP) expression. By demonstrating that APN up‐regulates MMP‐9 expression in resident cardiac and infiltrating immune cells we provide a novel mechanism how APN might inhibit adverse cardiac remodeling associated with MI, myocarditis, and overload states. Supplementary to a direct inhibition of local collagen expression, the APN‐induced up‐regulation of cardiac MMP‐9 activity results in increased cleavage of accumulating collagens and augmented ECM turnover that contributes to attenuation of LV fibrosis and dysfunction.